Pengaruh Program Bimbingan Kelompok terhadap Perilaku Disiplin Siswa di SD Negeri 1005 Sidomulio - Rizki Hamdan Saputra; Hidayat Nasution; Siti Maryam Hasibuan; Jamilah Fahma Pulungan; Ence daulay; Fitriana Dalimunthe; Doarni Lubis (JURNAL ILMIAH RESEARCH STUDENT, 2026)
This study aims to determine the effect of group counseling programs on student discipline at SD Negeri 1005 Sidomulio. Student discipline problems are still frequently encountered, such as tardiness, failure to comply with school rules, and lack of responsibility for school assignments. Group counseling programs are seen as one of the guidance and counseling services that can help students understand and apply discipline optimally. This study uses a quantitative approach with an experimental research design. The research population consists of all students at SD Negeri 1005 Sidomulio, with a sample of 48 students selected using a specific sampling technique. Data collection was conducted using a discipline behavior questionnaire that had been tested for validity and reliability. Data analysis techniques included validity testing, reliability testing, prerequisite analysis testing (homogeneity and linearity testing), simple linear regression analysis, t-testing, and coefficient of determination testing. The results of the study indicate that the group guidance program has a positive and significant effect on student discipline behavior. This is evidenced by the t-test results, which show a significance value lower than the predetermined significance level. In addition, the coefficient of determination results show that the group guidance program contributes significantly to improving student discipline behavior. Thus, the group guidance program can be used as an effective strategy for improving student discipline behavior in elementary schools.